End-of-life of silicon PV panels: A sustainable materials recovery process. (1st February 2019) - Fiandra, Valeria; Sannino, Lucio; Andreozzi, Concetta; Graditi, Giorgio
Highlights: A correct management of the PV waste allows the recovery of valuable materials. An energy-environmental sustainable heat treatment degrades the polymeric matter. Low emissions assure a good trade-off between technical and environmental targets. Fluorinated gaseous exhausts deriving from the Tedlar® burning are not produced. A slightly oxidizing atmosphere reduces organic emissions and particulate matter. Abstract: In this paper, the management of end-of-life PV modules based on an advanced eco-sustainable process has been presented and discussed. The thermal removal of the polymeric compounds contained in c-Si PV modules has been investigated to separate and recover Si, Ag, Cu, Al and glass. A two-step thermal process has been employed. In the first step, the rear polymeric layer has been removed without emissions of dangerous fluorinated substances. In the second step, the remaining polymers have been completely removed with low volatile organic compounds (VOCs) emissions. The polymers degradation has been studied at combustion equivalent ratios Φ varying from 0.5 to 2 and at 500 °C. The materials recovery has been evaluated from an environmental point of view and optimized by considering the energy cost, through the identification of the best operating conditions, in terms of temperature, time, atmosphere and gas flow. One hour of heat treatment and a slightly oxidizing atmosphere have been enabled to separate and recover the different materials of the module. The elemental compositions of the PV sample and the residue condensed organic products have been determined. The gaseous degradation products have been characterized by gas chromatographic analysis (GC).